PENGARUH TEKNIK SOSIODRAMA TERHADAP PENINGKATAN RESILIENSI SISWA KELAS X SMA NEGERI 4 PEKANBARU TAHUN AJARAN 2015/2016 - Ariyanti, Fitria; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research is to determine the influence of technic sociodrama towards students resilience at X class senior high school 4 pekanbaru year 2015/2016. This research take place at senior high school 4 pekanbaru from march 2016 to may 2016. The research method of this research is rea-experimental method with pretest-psttest control group design pattern. The subject of this research is the students at X class senior high school 4 pekanbaru with low resilience. The data accumulation instrument is questionnaire with likert scale. The data technic analysis is statistic correlation technic. Based on the test result of wilcoxon we can get the fact that there is a difference of students resilience before and after the sociodrama is 56,7%. Later, after the comparison between the experiment group and control group based on mann-whitney test resultthere is a significant difference of students resilience towards experiment group and students resilience towards control group.Key Words :Sociodrama technic, Resilience.